To plan or not to plan? An analysis of the impact of planning on the disbanding or growth of Brazilian start-ups. (1st January 2013) - Borges, Cândido; Hashimoto, Marcos; Limongi, Ricardo
This study analyses the relationship between the drawing up of plans for start-ups (under five years of age) and certain performance factors, such as survival, growth and acquiring capital. The empirical approach uses a secondary database composed of data from 1, 819 Brazilian start-ups. The data was processed by multivariate analysis using three groups of variables: performance as a dependent variable, planning as an independent variable, and other demographic data as control variables. The results indicate that planning does influence the survival and growth of enterprises, particularly in terms of collecting information, time taken to plan and the entrepreneur's perception of the importance of planning. The study showed that planning has no influence on the ability to raise financial resources.